Comparison of Intraoperative and Postoperative Outcomes of Proximal Femoral Nailing and Bipolar Hemiarthroplasty Techniques in Intertrochanteric Femur Fracture Treatment - Mehmet Yetiş; Emre Yurdakul (Düzce Tıp Fakültesi Dergisi, 2022)
Aim: This study was undertaken with the purpose of comparing the short and long term surgical, clinical, and functional results between bipolar hemiarthroplasty and proximal femoral nailing in the same cohort of patients. Material and Methods: The retrospective scanning of two-year data of a tertiary care hospital has been carried out for patients with hip fractures undergoing proximal femoral nailing and bipolar hemiarthroplasty. 67 patients underwent proximal femoral nailing and 74 patients underwent bipolar hemiarthroplasty were included in the study. Each patient's short and long term outcomes were documented as well as their preoperative, intraoperative, and postoperative features. Results: There were no significant differences in the demographic features of both groups. The median intraoperative blood loss was significantly higher in the group who underwent bipolar hemiarthroplasty compared to the group who underwent proximal femoral nailing (450 cc vs 300 cc, respectively, p<0.001). It was found that the bipolar hemiarthroplasty procedure was associated with a greater need for intraoperative transfusion than the proximal femoral nailing procedure (p=0.007). Intraoperative complications were reported only in patients who underwent bipolar hemiarthroplasty. The need for intensive care unit was significantly higher in the bipolar hemiarthroplasty group than in the proximal femoral nailing group, with the rate of 86.5% (n=64) and 68.7% (n=46), respectively (p=0.011). Conclusion: According to the results of this study, the proximal femoral nailing procedure appears to be a more reliable surgical technique in patients with hip fractures in terms of both intraoperative complications and the postoperative need for an intensive care unit.